Evaluation of normal tibial tubercle to trochlear groove distance in adult Turkish population - Ortuğ, Alpen; Örmeci?, Tu?rul; Yüzbaşıo?lu, Neslihan; Albay, Soner; Şeker, Muzaffer (Wolters Kluwer Medknow Publications, 2018)
Purpose: Many studies have confirmed the significance of tibial tuberosity-trochlear groove (TTTG) distance measurement for the preoperative assessment of tibial tubercle osteotomy and refixation of the patients that need surgery. TTTG distance is being used as threshold value for surgery decision. The purpose is to determine the TTTG values for the adult Turkish population and compare this with the values of other studies and establish a possible index. Materials and Methods: This study was conducted on 200 patients (97 female, 103 male) aged between 18 and 65 years, retrospectively, who had magnetic resonance imaging at Istanbul Medipol Mega University Hospital Radiology Department. Individuals with no knee surgical history and deformation included to research group, any deformities related with knee were excluded. The scans were analyzed in Picture Archiving Communication System program and compared with other populations. Significance was evaluated with independent Student's t-test. Results: The mean TTTG distance was found 10.07 +/- 1.60 mm in males, 9.96 +/- 1.41 mm in females, and 10.02 +/- 1.51 mm for total cases. There was no statistically significant difference between sex (P > 0.05). However, overall TTTG distance of right and left knees found significantly different (P < 0.05). Conclusion: Obtained results are similar with the results of Caucasian population but different than Asian. It is believed that these results will be significant in evaluation of patellofemoral disorders and helpful in treatment.
WOS: 000450148600003
PubMed ID: 30417836
Keywords: Knee Joint; Magnetic Resonance Imaging; Patellar Dislocation; Sexual Dimorphism; Tibial Tuberosity-Trochlear Groove; Turkish Population